Effect of Copper, Zinc, and Selenium on the Migration of Bovine Neutrophils - Hai Wang; Guanxin Lv; Shuai Lian; Jianfa Wang; Rui Wu (Veterinary Sciences, 2021)
Neutrophils represent the first line of mammary gland defense against invading pathogens by transmigration across the mammary epithelial cell barrier. The effect of trace elements on the migration of bovine neutrophils is not clear. In this study, we investigated the effect of copper (Cu; 0.5, 1.0 and 1.5 mg/L), zinc (Zn; 1.0, 5.0 and 10 mg/L) and selenium (Se; 0.1, 1.0 and 2.0 mg/L) on the migration of bovine neutrophils by using a Transwell assay. The results showed that Cu, Zn and Se promoted the number of neutrophils in the trans-mammary epithelium. With the increased concentration of Cu at 1.5 mg/L, the number of neutrophils in the trans-mammary epithelium was increased significantly (p < 0.05). Zn (5.0 mg/L) and Se (0.1 mg/L) increased the migrated number of neutrophils (p < 0.01) to an extremely significant degree. These findings provided a theoretical and experimental basis for mammary gland immunity in dairy cows. Thus, we suggest that adding moderate amounts of different trace elements can improve the immune function of dairy cows.